Peran Pencahayaan Terhadap Suasana Ruang Interior Beehive Boutique Hotel Bandung - Wulandari, Risti R; Isfiaty, Tiara (DIVAGATRA - Jurnal Penelitian Mahasiswa Desain, 2021)
This research aims to find out the influence of lighting roles to create an atmosphere that can describe a particular theme or styling applied to the design of the Beehive Boutique Hotel space so that it can be seen, felt, and observed visualized by space users or space observers. Lighting is an important element to bring atmosphere and character to an interior space. There are many types of lighting that can be applied to the interior room and depending on what atmosphere the user wants to feel. Lighting can also support visualization of the style applied to the room. The method used in this study is observation and comparison based on the theory used in the research. The results and conclusions drawn are described descriptively according to observations made by researchers by comparing them to the theory used. The conclusion is that the lighting role applied to the Beehive Boutique Hotel's interior space can help create an atmosphere that depicts scandinavian themes or sytles applied to the hotel's interior.